Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Terhadap Perataan Laba Dengan Good Corporate Governance Sebagai Variabel Moderasi - Michael Owen Sihotang; Wikan Isthika; Entot Suhartono; Dian Indriana Hapsari (CV. Ulil Albab Corp, 2024)
A tactic used by management to keep profits steady over time and frequently driven by executive remuneration is income smoothing. When bonuses are dependent on the company's profitability, managers may utilize income smoothing to guarantee they keep getting the promised bonuses from the owners. In addition to examining whether management ownership can mitigate these correlations. This study seeks to examine the relationship between profitability, leverage, and firm size in relation to income smoothing. The Eckel index is employed to measure income smoothing, while managerial ownership is determined by the ratio of managers shareholdings to the firm's total assets. Profitability is quantified using Return on Assets (ROA), leverage by the Debt to Equity Ratio (DER), and firm size by the natural logarithm of total assets. The analysis reveals that leverage exerts a negative effect on income smoothing, whereas neither profitability nor firm size significantly influence this practice. These conclusions are drawn from logistic regression analysis conducted using SPSS 25. Moreover, the study finds that managerial ownership does not moderate the relationship between profitability, leverage, and firm size in the context of income smoothing.